2016
DOI: 10.1099/ijsem.0.000716
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces actinomycinicus sp. nov., isolated from soil of a peat swamp forest

Abstract: A novel actinomycete, strain RCU-197 T , was isolated from soil of a peat swamp forest in Rayong Province, Thailand. Using a polyphasic approach, the strain was classified in the genus Streptomyces. It contained LL-diaminopimelic acid in the cell-wall peptidoglycan. No diagnostic sugars were detected in whole-cell hydrolysates and there was a lack of mycolic acids. The major menaquinones were MK-9(H 6 ) and MK-9(H 8 ). The predominant cellular fatty acids were iso-C 14 : 0 , iso-C 15 : 0 , anteiso-C 15 : 0 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…The major menaquinones were MK-9(H 8 ) (53.8 %), MK-9(H 6 ) (28.7 %), and MK-9(H 4 ) (13.4 %) while MK-10(H 4 ) (3.3 %), MK-10(H 2 ) (0.8 %) were also observed. The major menaquinone of CH5-8 T was similar to the major menaquinones found in S. actinomycinicus RCU-197 T [48]. Diphosphatidylglycerol (DPG), phosphatidylethanolamine (PE), hydroxyphosphatidylethanolamine (OH-PE), phosphatidylglycerol (PG), phosphatidylinositol (PI), phosphatidylinositol mannoside (PIM), four unidentified phospholipids (PLs) and two unidentified lipids (Ls) were observed as the polar lipids in cells (Fig.…”
Section: Resultssupporting
confidence: 66%
“…The major menaquinones were MK-9(H 8 ) (53.8 %), MK-9(H 6 ) (28.7 %), and MK-9(H 4 ) (13.4 %) while MK-10(H 4 ) (3.3 %), MK-10(H 2 ) (0.8 %) were also observed. The major menaquinone of CH5-8 T was similar to the major menaquinones found in S. actinomycinicus RCU-197 T [48]. Diphosphatidylglycerol (DPG), phosphatidylethanolamine (PE), hydroxyphosphatidylethanolamine (OH-PE), phosphatidylglycerol (PG), phosphatidylinositol (PI), phosphatidylinositol mannoside (PIM), four unidentified phospholipids (PLs) and two unidentified lipids (Ls) were observed as the polar lipids in cells (Fig.…”
Section: Resultssupporting
confidence: 66%
“…Actinomycin D is a secondary metabolite produced by many streptomycetes, including S. actinomycinicus RCU-197 T , the closest related strain of PJ85 ( Figure 1 ). It has been reported that the sole antibacterial agent produced by S. actinomycinicus RCU-197 T is actinomycin D [ 30 ]. However, an unidentified bioactive agent, compound 2, was also detected from the PJ85 crude extract ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Carbon-nitrogen sources can also be added to the isolation media; casein [55,56], peptone [8,57], malt extract [58] and yeast extract [53,58,59]. The isolation media can be supplemented by K 2 Cr 2 O 7 [54,[60][61][62][63][64], nalidixic acid, nystatin, cycloheximide, rifampicin, and tetracycline [37,38,40,49,51,53,55,56,58,59,[65][66][67][68][69] to inhibit the growth of unwanted bacteria and fungi (See Tables 1 and S1).…”
Section: Extreme Environmentsmentioning
confidence: 99%
“…This is advantageous when performing pretreatments to selectively isolate Streptomyces spp. Some of the commonly used pretreatments for the isolation of Streptomyces from an extreme terrestrial environment include distilled water with added NaCl [38,52,71,72], air-drying [53,64,68] pretreatment by ultrasound [56,69] and agitation on a rotary stirrer [37,40,54,57,66,69]. Dry heat treatment and wet heat treatment are the most frequently used pretreatments.…”
Section: Extreme Environmentsmentioning
confidence: 99%